2018
DOI: 10.1111/eve.12935
|View full text |Cite
|
Sign up to set email alerts
|

Successful outcome of a Standardbred filly after conservative treatment for a Salter–Harris typeIIIfracture of the distal femoral condyle

Abstract: Summary A 10‐day‐old Standardbred filly sustained a complex Salter–Harris type III fracture of the right, lateral, distal femoral condyle. The lateral condyle was fractured in transverse, sagittal and frontal planes. The filly was treated by restricting it and its dam to a small, level paddock until lameness was no longer apparent. The filly, when weaned at 7 months of age, was turned out to pasture with three other weanlings. The filly entered race training as a 2‐year‐old, qualified to race as a trotter, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While it is known that physeal fractures can heal rapidly, for any particular case it is unknown whether the injured physis will resume symmetrical longitudinal growth, grow asymmetrically and result in an angular deformity, or close prematurely due to significant damage or blood supply compromise. Follow-up radiographs of the foal in the report by Valk and Schumacher (2020) performed at 13 months of age showed that the distal femoral physis was closed and the proximal tibial growth plate was open but thin. Radiographic closure time for the distal femoral physis is reported as 19-27 months of age, while the proximal tibial physis closure occurs from 23 to 32 months of age (Strand et al 2007).…”
Section: The Complexity Of Physeal Fracturesmentioning
confidence: 96%
See 3 more Smart Citations
“…While it is known that physeal fractures can heal rapidly, for any particular case it is unknown whether the injured physis will resume symmetrical longitudinal growth, grow asymmetrically and result in an angular deformity, or close prematurely due to significant damage or blood supply compromise. Follow-up radiographs of the foal in the report by Valk and Schumacher (2020) performed at 13 months of age showed that the distal femoral physis was closed and the proximal tibial growth plate was open but thin. Radiographic closure time for the distal femoral physis is reported as 19-27 months of age, while the proximal tibial physis closure occurs from 23 to 32 months of age (Strand et al 2007).…”
Section: The Complexity Of Physeal Fracturesmentioning
confidence: 96%
“…As a result, soft tissue injury and subsequent healing, which invariably accompany physeal fracture, also contribute to the rapid return of stability in this region of the bone. The degree of soft tissue support surrounding the fracture in the report by Valk and Schumacher () was likely one reason that the fracture remained minimally displaced and healed without long‐term complications.…”
Section: The Complexity Of Physeal Fracturesmentioning
confidence: 98%
See 2 more Smart Citations
“…The foal should be returned to normal pasture turnout as soon as possible based on an individual assessment of the temperament of the mare and foal, the progress of the condition and rehabilitation, and the home facilities. As discussed by Lescun (2018), foals change their exercise behaviour significantly when confined, and pasture turnout may ensure a more continuous low‐impact strain on their musculoskeletal system, as opposed to the less controllable bursts of high impact strain sometimes seen when foals are confined in a stall or only turned out for shorter periods of time (Valk and Schumacher 2020). However, if long periods of confinement have been necessary, unrestricted pasture turnout should be introduced carefully, as catastrophic fractures of the sesamoid bones have been described in recovered foals or foals that run to exhaustion trying to keep up with the dam (Reesink 2017).…”
Section: Rehabilitationmentioning
confidence: 99%